Effects of paint thinner exposure on serum LH, FSH and testosterone levels and hypothalamic catecholamine contents in the male rat - Yilmaz, B; Kutlu, S; Canpolat, S; Sandal, S; Ayar, A; Mogulkoc, R; Kelestimur, H (Pharmaceutical Soc Japan, 2001)
We have investigated the effects of thinner inhalation an serum LH, FSH and testosterone levels together with changes in hypothalamic catecholaminergic system in the male rat. A control group inhaled normal air ventilation. The remaining animals were divided into two groups and exposed to paint thinner in a glassy cage for 15 or 30 d. Toluene concentration (the largest constituent in thinner, 66%) was set at 3000 ppm in the inhalation air. At the end, all animals were decapitated and blood samples obtained. Serum LH and FSH levels were measured by RIA and testosterone by enzyme immunoassay. Following removal of brains on dry ice, medial preoptic area, suprachiasmatic nucleus, median eminence and arcuate nucleus were isolated by micropunch technique. Noradrenaline, 3,4-dihydroxyphenylglycol (DHPG) and dopamine concentrations of these hypothalamic areas were determined by HPLC-ECD. Fifteen-day thinner inhalation significantly suppressed serum LH and testosterone levels in parallel (p<0.001) compared to control group values (LH: 0.77+/-0.07; testosterone: 2.67+/-0.39). Thirty-day exposure markedly decreased LH levels (p<0.001), but surprisingly had no significant effect on testosterone. Serum FSH levels were not significantly altered in either group. Thinner inhalation for 15 or 30 d did not cause any significant change in noradrenaline, DHPG or dopamine concentrations in the hypothalamic regions examined (except in the arcuate nucleus). These results suggest that paint thinner has an anti-gonadotropic effect and may cause long-term endocrine disturbances in the male. It is thought that the hypothalamic catecholaminergic system is not involved in thinner inhibition of LH and testosterone secretion.
Keywords: paint thinner; gonadotropin; testosterone; noradrenaline; dopamine